Isolation, fractionation and evaluation of the antiplasmodial properties of Phyllanthus niruri resident in its chloroform fraction - Ifeoma, Obidike; Samuel, Okhale; Itohan, Aboh Mercy; Adeola, Salawu Oluwakanyinsola (Asian Pacific Journal of Tropical Medicine, 2013)
Objective: To investigate the antiplasmodial activity of Phyllanthus niruri (P. niruri) methanol extract (ME) and its fractions in mice. Methods: P. niruri methanol extract and its chloroform, ethanol and aqueous portions were tested against chloroquine-sensitive Plasmodium berghei berghei. in early, established mid repository models of infection using Knight and Peter's 4-day suppressive model, Ryley and Peters curative model and Peters prophylactic model respectively. Results: Chemosuppression of parasitaemia (37.65%-50.53 %) was elicited by 100-400 mg/kg (b.w.) of ME. At doses of 100 mg/kg b.w., the chloroform fraction (F1) significantly (P<0.01) suppressed parasitaemia by 85.29%, while ethanol and aqueous fractions (F2 and F3, respectively) elicited 67.06% and 51.18% chemosuppression. The most active fraction, F1 was selected for further antiplasmodial screening. In established infection, ME reduced parasitaemia (15.81%-62.96%) while F1 significantly (P<0.01) reduced parasitaemia (44.36%-90.48%), with effects comparable to that of chloroquine (96.48%). The prophylactic antiplasmodial activity of ME (92.50% suppression) was also significant (P<0.01) and was more effective than pyrimethamine (85.00%). Additionally, cell membrane integrity of non-parasitized erythrocytes incubated with 125-500 mg/mL F1 was maintained. Conclusions: These findings indicate the antiplasmodial efficacy of P. niruri methanol extract, and the localization of this effect in its chloroform fraction.
Keywords: malaria; Phyllanthus niruri; Plasmodium